UV-Cured Reactive Mesogen-YInZnO Hybrid Materials as Semiconducting Channels in Thin-Film Transistors Using a Solution-Process. (1st January 2015) - Kim, Seon Yeong; Jung, Yoon Ho; Cho, Min-Jae; Lee, Jae-Won; Park, Hong-Gyu; Kim, Dai-Hyun; Kim, Tae Wan; Yun, Ilgu; Seo, Dae-Shik
Abstract : Electrical performance of thin-film transistors (TFTs) is important for their applications. Solution-processed TFTs have low mobility and high sub-threshold swings (S.Ss) because there are many pores and pin-holes in the films. These characteristics are attributed to electron trapping in the YInZnO (YIZO) channel, the SiO2 gate insulator, or their interface. We fabricated hybrid YIZO TFTs with and without UV radiation, and observed that UV-curing of the film affected TFT performance through promoting a response to reactive mesogen (RM). The UV irradiated TFT showed better performance because of the alignment of the channel materials in the source-drain direction.